Meibomian Gland Assessment in Routine Ophthalmology Practice - Igor Petriček; Martina Tomić; Tomislav Bulum; Dina Lešin Gaćina; Sania Vidas Pauk (Metabolites, 2023)
This cross-sectional study aimed to investigate the connection between meibomian gland (MG) excreta quantity and quality after MG expression (MGX), dry eye disease (DED) symptoms, and objective DED signs and to clarify the relationship between dry eye and MG function in DED pathophysiology. The study included 200 subjects, 100 with and 100 without dry eye symptoms. Schein questionnaire was used to determine the severity of dry eye symptoms and self-reported skin type for facial skin dryness self-evaluation. Objective dry eye signs were assessed by monitoring conjunctival hyperemia, lid parallel conjunctival folds (LIPCOF), tear break-up time (TBUT), fluorescein surface staining and digital MGX. Subjects with DED symptoms had significantly lower MG quantity scores than healthy controls (p < 0.001). Meibum quality and quantity scores significantly correlated with female gender (p = 0.002), Schein questionnaire score (p < 0.001), fluorescein corneal staining score (p = 0.019), self-reported skin type (p < 0.001), TBUT (p < 0.001) and LIPCOF (p = 0.041). After adjustment for age and gender in a logistic regression analysis, dry eye was independently and significantly associated with self-reported skin type (OR 0.73, p < 0.001), LIPCOF (OR 1.04, p < 0.001), fluorescein corneal staining (OR 1.05, p = 0.019), TBUT (OR 0.77, p < 0.001) and meibum quantity score (OR 0.59, p < 0.001). Dry eye symptoms and objective signs correlated well in this study. MGX discriminated between the subjects with and without DED symptoms and was associated with other objective DED signs. Results showed a significant association between meibum quality and quantity, MG function, DED and facial skin dryness self-perception. This paper established a correlation between dry eye symptoms caused by MG dysfunction and dry skin, which can help general health practitioners consider dry eye as a cause of chronic eye complaints with patients who report dry skin.